Embolisasi Pra Operatif Untuk Angiofibroma Nasofaringeal - Abdillah, Fauzan; Nugroho, Dwi Agustawan; Fadillah, Ibnu Harris; Mashabi, Yasmine; Yousif, Emad; Hairunisa, Nany (Jurnal Biomedika dan Kesehatan, 2025)
Background: Juvenile nasopharyngeal angiofibroma (JNA) is a rare benign vascular tumor that almost exclusively affects adolescent males. Despite its benign nature, JNA demonstrates locally aggressive behavior and is associated with significant intraoperative bleeding. Preoperative embolization has become an important modality to reduce tumor vascularization and minimize intraoperative blood loss. The Objective of this case report is to discuss the role of preoperative embolization in the management of JNA, including relevant vascular anatomy, embolic materials, benefits and limitations, as well as local case experiences in Indonesia. Methods: A literature review was conducted on the external carotid artery anatomy, etiology, epidemiology, histopathology, tumor spread and staging, and preoperative embolization techniques using various materials such as gelfoam, polyvinyl alcohol, ethanol, and microspheres. Additionally, two cases of JNA at Cipto Mangunkusumo Hospital were reported, both treated with preoperative embolization using gelfoam prior to transpalatal tumor resection. Results: In both cases, embolization successfully reduced tumor vascularity. However, due to surgical delay beyond 48 hours after embolization, intraoperative bleeding remained significant (800–1000 mL). Both patients recovered uneventfully without postoperative complications, and histopathological findings confirmed JNA. Conclusion: Preoperative embolization is effective in reducing intraoperative blood loss during JNA surgery and should ideally be performed within 24–48 hours before resection. This approach facilitates safer tumor removal, although its optimal success depends on timing, embolization technique, and operator expertise.